2014
DOI: 10.1007/s10646-014-1209-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of suitable qPCR reference genes in leaves of Brassica oleracea under abiotic stresses

Abstract: Real-time quantitative PCR is nowadays a standard method to study gene expression variations in various samples and experimental conditions. However, to interpret results accurately, data normalization with appropriate reference genes appears to be crucial. The present study describes the identification and the validation of suitable reference genes in Brassica oleracea leaves. Expression stability of eight candidates was tested following drought and cold abiotic stresses by using three different softwares (Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…As noted previously, CYP was the worst reference gene in a diverse pool of poplar [32], however the optimal stability of CYP expression identified in our study was in agreement with the result of Petunia hybrid transcriptomic analysis [33]. Additionally, the observations on the reference genes ACT , UBQ and RPL2 with stable expression in peach (Rosaceae) [34], Brassica oleracea [35] and tomato [28], respectively, had been completely verified in our studies. It has been reported that ELFA was the most stable in potato during biotic and abiotic stress [36], but poorly ranked during light stress in tomato [28].…”
Section: Discussionsupporting
confidence: 92%
“…As noted previously, CYP was the worst reference gene in a diverse pool of poplar [32], however the optimal stability of CYP expression identified in our study was in agreement with the result of Petunia hybrid transcriptomic analysis [33]. Additionally, the observations on the reference genes ACT , UBQ and RPL2 with stable expression in peach (Rosaceae) [34], Brassica oleracea [35] and tomato [28], respectively, had been completely verified in our studies. It has been reported that ELFA was the most stable in potato during biotic and abiotic stress [36], but poorly ranked during light stress in tomato [28].…”
Section: Discussionsupporting
confidence: 92%
“…To estimate the expression stability of reference genes, we measured the relative quantities of crossing point values of genes obtained using the formula of Hellemans et al [30]. The geometric mean of the 3 most stable reference genes in cupric condition was used to calculate expression of target gene levels according to Brulle et al [35]. The procedures of the analyses strictly followed the manuals of BestKeeper, version 1 [32], NormFinder, version 5 [33], and geNorm, version 3.5 [34] algorithms.…”
Section: Rna Isolation Cdna Synthesis Housekeeping Genes Validationmentioning
confidence: 99%
“…The average of cycle threshold (Ct) values and expression levels of each candidate reference gene in 10 different date palm hypocotyl stressed samples were transferred to software, as fully described by Brulle et al [35]. The average of cycle threshold (Ct) values and expression levels of each candidate reference gene in 10 different date palm hypocotyl stressed samples were transferred to software, as fully described by Brulle et al [35].…”
Section: Internal Reference Gene Validation For Qpcr Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, HKGs, such as actin (ACT), b-tubulin (TUB), GAPDH, polyubiquitin, and elongation factor 1-a (EF1-a) (Bustin 2002;Radonic et al 2004;Czechowski et al 2005;Gutierrez et al 2008b), whose protein products are supposed to have stable and uniform expression across different tissues and developmental stages, are commonly used as internal reference genes (Paolacci et al 2009). However, recent studies have suggested that the expression of these genes can vary significantly under different environmental conditions (Thellin et al 1999;Schmittgen and Zakrajsek 2000;Suzuki et al 2000;Brulle et al 2014). Therefore, it is necessary to identify the internal reference gene(s) for the efficient quantification of a target mRNA in a given set of biological samples by qRT-PCR.…”
Section: Introductionmentioning
confidence: 99%